2015
DOI: 10.1097/ta.0000000000000792
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced systemic hyperfibrinolysis is attenuated by plasma-first resuscitation

Abstract: Background We developed a hemorrhagic shock animal model to replicate an urban prehospital setting where resuscitation fluids are limited to assess the effect of saline versus plasma in coagulopathic patients. An in vitro model of whole blood dilution with saline exacerbated tPA mediated fibrinolysis, while plasma dilution did not change fibrinolysis. We hypothesize that shock induced hyperfibrinolysis can be attenuated by resuscitation with plasma while exacerbated by saline. Methods Sprague Dawley rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 40 publications
4
39
0
Order By: Relevance
“…In current clinical practice, early empiric plasma resuscitation appears to be a rationale approach for hypotensive trauma trauma patients as it is a buffer of fibrinolysis(42). Animal models have shown that plasma attenuates hemorrhagic shock induced hyperfibrinolysis (43) and reduces post resuscitation hypercoagulability(44). Ultimately, the debate on the optimal ratios of blood components for initial resuscitation has not become as critical as the timing of early plasma administration.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, early empiric plasma resuscitation appears to be a rationale approach for hypotensive trauma trauma patients as it is a buffer of fibrinolysis(42). Animal models have shown that plasma attenuates hemorrhagic shock induced hyperfibrinolysis (43) and reduces post resuscitation hypercoagulability(44). Ultimately, the debate on the optimal ratios of blood components for initial resuscitation has not become as critical as the timing of early plasma administration.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is an effective buffer of fibrinolytic activity (19) and effectively reverses hyperfibrinolysis and reduces mortality in hyperfibrinolytic rodents (20). This effective colloid also has been shown to enhance metabolic recovery (21) from hemorrhagic shock, restore the endothelial glycoalyx (22), reduce pulmonary injury (23) and reduce gastrointestinal damage (24).…”
Section: Discussionmentioning
confidence: 99%
“…14 Prehospital plasma infusion has been shown to be feasible during helicopter transport, 15 but the logistics of storage and thawing in fast ground transport have been challenging. 1,16 Anticipation of approval of the lyophilised plasma by the US Food and Drug Administration (FDA) prompted the US Department of Defense to fund several randomised controlled trials across the USA to produce robust evidence on early plasma resuscitation.…”
Section: Introductionmentioning
confidence: 99%